Friends of the unrighteous mammon : northern Christians and market capitalism, 1815-1860 - Davenport, Stewart (University of Chicago Press, 2008)
The Bible told antebellum Christians that they could not serve both God and Mammon, but in the midst of the market revolution of the 19th century, most of them held on to their faith while simultaneously working furiously to make a place for themselves in a changing economic climate. Davenport examines this paradoxical partnership.